Association of Time of Day When Endovascular Therapy for Stroke Starts and Functional Outcome. (23rd February 2021) - Hajdu, Steven D.; Kaesmacher, Johannes; Michel, Patrik; Sirimarco, Gaia; Knebel, Jean-Francois; Bartolini, Bruno; Kurmann, Christoph C.; Puccinelli, Francesco; Mosimann, Pascal J.; Bonvin, Christophe; Arnold, Marcel; Niederhäuser, Julien; et al.
Abstract : Objective: To investigate the association between endovascular therapy (EVT) start time in acute ischemic stroke (AIS) and midterm functional outcome. Methods: This retrospective cohort study included all patients with AIS treated with EVT from 2 stroke center registries from January 2012 to December 2018. The primary outcome was the score on the modified Rankin Scale (mRS) and the utility-weighted mRS (uw-mRS) at 90 days. A proportional odds model was used to calculate the common odds ratio (OR) as a measure of the likelihood that the intervention at a given EVT start time would lead to lower scores on the mRS (shift analysis). Results: A total of 1, 558 cases were equally allotted into 12 EVT start time periods. The primary outcome favored EVT start times in the morning at 08:00–10:20 and 10:20–11:34 (OR, 0.53; 95% confidence interval [CI], 0.38 to 0.75; p < 0.001; OR, 0.62; 95% CI, 0.44 to 0.87; p = 0.006, respectively), while it disfavored EVT start times at the end of the working day at 15:55–17:15 and 18:55–20:55 (OR, 1.47; 95% CI, 1.03–2.09; p = 0.034; OR, 1.49; 95% CI, 1.03–2.15; p = 0.033). Symptom onset to EVT start time was significantly higher and use of IV tissue plasminogen activator significantly lower between 10:20 and 11:34 ( p < 0.004 and p = 0.012, respectively). Conclusion: EVT for AIS in the morning leads to better midterm functional outcome, while EVT at the end of the work day leads to poorer midterm functional outcome. Difference in baseline factors, standard workflow, and technical efficacy metrics could not be identified as potential mediators of this effect.